A study on communication among foreign worker at construction site - Muhammad Hadi, Asmuni (2015)
The study has identified about effective communication between migrant workers in the construction industry in Johor. The objective of this study was to determine the language used among migrant workers at construction sites and identify the role of the organization to achieve effective communication between migrant workers at construction sites which are in the construction industry in Johor. In addition, the literature describes the importance of effective communication in the construction industry involving foreign workers on a construction site. Barriers to communication between migrant workers is caused by factors which language is used. This is because the foreign workers come from different countries at the same time the state is difficult to communicate with people of different nationalities. Furthermore, there is a solution to this problem and involving the role of an organization to create an effective communication between migrant workers at a construction site. Therefore, the results obtained show that the Malay language is used as a language of communication and organization are also important role in solving these problems. The result can also be used for other industries to establish an effective communication involving migrant workers.